2011
DOI: 10.2119/molmed.2010.00091
|View full text |Cite|
|
Sign up to set email alerts
|

High-Glucose Environment Inhibits p38MAPK Signaling and Reduces Human β-3 Expression in Keratinocytes

Abstract: Diabetes mellitus is characterized by elevated plasma glucose and increased rates of skin infections. Altered immune responses have been suggested to contribute to this prevalent complication, which involves microbial invasion. In this study we explored the effects of a high-glucose environment on the innate immunity of keratinocytes by focusing on β defensin-3 (BD3) using in vivo and in vitro models. Our results demonstrated that the perilesional skins of diabetic rats failed to show enhanced BD3 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…These results corroborated with a previous study showing that EGFR-ERK cascade regulates the production of IL-8 in lung cancer cells (24). It should be noted that our experimental condition did not significantly alter the physiologic status (viability, growth, and differentiation) of culture keratinocytes as demonstrated in our previous study (21). …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These results corroborated with a previous study showing that EGFR-ERK cascade regulates the production of IL-8 in lung cancer cells (24). It should be noted that our experimental condition did not significantly alter the physiologic status (viability, growth, and differentiation) of culture keratinocytes as demonstrated in our previous study (21). …”
Section: Discussionsupporting
confidence: 58%
“…1 C ) It has been reported that nuclear factor-κB (NF-κB), p38 MAPK, and ERK are involved in IL-8 secretion of keratinocytes (22,23). Since we had previously demonstrated that upregulation of NF-κB and p38 MAPK was not observed in high glucose–cultivated keratinocytes (21), we focused on ERK signaling. As demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HBD3 is highly expressed in keratinocytes, especially at wound sites in response to the growth factors such as EGF, transforming growth factor-α, and insulin growth factor-1 [310][311][312], and it has been shown that the peptide promotes the proliferation and migration of keratinocytes through phosphorylation of the EGF receptor and STAT proteins [289]. However, this study also showed that when the skin of diabetic rats was wounded, RBD3 induction was negligible and similar observations were made for HBD3 expression in human keratinocytes under various glucose-treatment conditions, indicating that both defensins were dysfunctional under hyperglycemic conditions [313]. However, this study also showed that when the skin of diabetic rats was wounded, RBD3 induction was negligible and similar observations were made for HBD3 expression in human keratinocytes under various glucose-treatment conditions, indicating that both defensins were dysfunctional under hyperglycemic conditions [313].…”
Section: Defensins and Wound Healingsupporting
confidence: 73%
“…Specifically, p38 MAPK has been shown to play an important role in hBD2 and hBD3 production in epithelial cells such as keratinocytes [16], [17]. We thus hypothesized that p38 MAPK might be the downstream molecule of TLR2 involved in the induction of hBDs by LP01.…”
Section: Resultsmentioning
confidence: 96%